Charting a New Course Through Meaningful Occupation - Jennifer K. Fortuna (Open Journal of Occupational Therapy, 2020)
Rory Odom, an artist and United States Marine Corps Veteran based in Florida, provided the cover art for the Spring 2020 issue of The Open Journal of Occupational Therapy (OJOT). “Turtles All the Way Down” is an 8”x10” oil painting on canvas. After a tragic accident changed the course of Rory’s life, painting gave him hope. During rehabilitation, Rory sought opportunities to challenge himself and build technical skill as a painter. His bold use of color and signature impressionist style convey emotion and movement. In the face of adversity, meaningful occupation helped Rory chart a new course in life.